Radiation Tolerant Interfaces: Influence of Local Stoichiometry at the Misfit Dislocation on Radiation Damage Resistance of Metal/Oxide Interfaces. Issue 14 (24th April 2017) - Shutthanandan, Vaithiyalingam; Choudhury, Samrat; Manandhar, Sandeep; Kaspar, Tiffany C.; Wang, Chongmin; Devaraj, Arun; Wirth, Brian D.; Thevuthasan, Suntharampilli; Hoagland, Richard G.; Dholabhai, Pratik P.; Uberuaga, Blas P.; Kurtz, Richard J.
Abstract : The interaction of radiation with materials controls the performance, reliability, and safety of many structures in nuclear power systems. Revolutionary improvements in radiation damage resistance may be attainable if methods can be found to manipulate interface properties to give optimal interface stability and point defect recombination capability. To understand how variations in interface properties such as misfit dislocation density and local chemistry affect radiation‐induced defect absorption and recombination, a model system of metallic Cr x V1− x (0 ≤ x ≤ 1) epitaxial films deposited on MgO(001) single crystal substrates has been explored. By controlling film composition, the lattice mismatch between the film and MgO is adjusted to vary the misfit dislocation density at the metal/oxide interface. The stability of these interfaces under various irradiation conditions is studied experimentally and theoretically. The results indicate that, unlike at metal/metal interfaces, the misfit dislocation density does not dominate radiation damage tolerance at metal/oxide interfaces. Rather, the stoichiometry and the location of the misfit dislocation extra half‐plane (in the metal or the oxide) drive radiation‐induced defect behavior. Together, these results demonstrate the sensitivity of defect recombination to interfacial chemistry and provide new avenues for engineering radiation‐tolerant nanomaterials for next‐generation nuclear power plants. Abstract : By controlling Cr x V1− x alloy film composition, the lattice mismatch with MgO single crystal is adjusted so that the misfit dislocation density varies at the epitaxial Cr x V1− x alloy film/MgO interface. These interfaces are exposed to irradiation and in situ and ex situ results show that the film with a semicoherent interface withstands irradiation up to 100 dpa.